2015
DOI: 10.1371/journal.pone.0130985
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Muscle Architecture and Comprehensive Dynamic Properties of Rabbit Gastrocnemius, Plantaris and Soleus: Input for Simulation Studies

Abstract: The vastly increasing number of neuro-muscular simulation studies (with increasing numbers of muscles used per simulation) is in sharp contrast to a narrow database of necessary muscle parameters. Simulation results depend heavily on rough parameter estimates often obtained by scaling of one muscle parameter set. However, in vivo muscles differ in their individual properties and architecture. Here we provide a comprehensive dataset of dynamic (n = 6 per muscle) and geometric (three-dimensional architecture, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 81 publications
(113 reference statements)
12
42
1
Order By: Relevance
“…Many studies have reported a linear rise in tension for moderate muscle lengthening that is independent of contraction speed for whole muscles [22][23][24], across muscle fibre bundles [25,26], down to intact single fibres [18]. These findings agree with the idea of a passive, spring-like contribution of, for example, titin to total muscle force.…”
Section: Introductionsupporting
confidence: 70%
“…Many studies have reported a linear rise in tension for moderate muscle lengthening that is independent of contraction speed for whole muscles [22][23][24], across muscle fibre bundles [25,26], down to intact single fibres [18]. These findings agree with the idea of a passive, spring-like contribution of, for example, titin to total muscle force.…”
Section: Introductionsupporting
confidence: 70%
“…By this filter selection, the signal noise was effectively reduced without changing the characteristics of the trajectories. In accordance with previous findings, we assumed the ascending limb of the force-length relationship to be linear (Blix, 1894;Gordon et al, 1966;Siebert et al, 2015). Therefore, least-squares linear regressions were used to determine the relationships between muscle length, isometric force, and intermuscular pressure in the ascending limb.…”
Section: Data Analysesmentioning
confidence: 77%
“…The study was conducted on the basis of well-established methods and procedures to determine muscle properties and deformations that have already been described in detail (Böl et al, 2013(Böl et al, , 2015Siebert et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations